Exoplanets: Gaia and the importance of ground based spectroscopy follow-up. Issue 67 (17th July 2015) - Benamati, L.; Adibekyan, V. Zh.; Santos, N.C.; Sozzetti, A.
Abstract : The search for extrasolar planets has developed rapidly and, today, more than 1700 planets have been found orbiting stars. Thanks to Gaia, we will collect high-accuracy astrometric orbits of thousands of new low-mass celestial objects, such as extra-solar planets and brown dwarfs. These measurements in combination with spectroscopy and with present day and future extrasolar planet search programs (like HARPS, ESPRESSO) will have a crucial contribution to several aspects of planetary astrophysics (formation theories, dynamical evolution, etc.). Moreover, Gaia will have a strong contribution on the stellar chemical and kinematic characterisation studies. In this paper we present a short overview of the importance of Gaia in the context of exoplanet research. As preparatory work for Gaia, we will then present a study where we derived stellar parameters for a sample of field giant stars.